Indicators of oxygen transport in acute and early periods of traumatic disease with multistage surgical correction at polytrauma - Matvieienko, Mariia (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Disorders of the oxygen transport play an important role in the development of multiple organ disfunction syndrome and are a marker of tissue hypoxia and ischemia. Disorders of the oxygen transport could be use for predicting patient survival and as criteria for the severity of the pathological process. The aim of this study was to explore the indicators of systemic oxygen transport in the perioperative period in patients with traumatic deases in multi-stage surgical correction at polytrauma in terms of standard and advanced intensive care. Materials and methods. A prospective study of 88 patients with traumatic deases was conducted. The dynamics of indices of oxygen delivery (iDО2) and oxygen consumption (iVO2), oxygen extraction coefficient (KEO2) at different variants of intensive care was studied. Results. The patients in both groups was noted iDO2 decline, which was due to massive blood loss and decreased cardiac output on admission to the operation room. Despite the fact that during the acute period was held stop bleeding, correction of hypovolemia and posthemorrhagic anemia, the average level of iDО2 was quite low. iDO2 was multidirectional nature of the changes in the studied groups at the second and third stages of the study. In turn, the average values KEO2 characterized the degree of tension compensatory mechanisms and metabolic changes caused by hypoxia and hypoperfusion. Normalization of oxygen homeostasis parameters was achieved in the fourth stage of the study. Conclusions. The maximal intensity of development of compensatory mechanisms and changes of oxygen transport occurs within the first 5 days after the injury. The optimized intensive care which has been used in the treatment patients of Group II, has positive effect on the ability to potentiate adaptive defense mechanisms and reduce oxygen debt.